Effect of dripper discharge on spatio-temporal movement of water in soil under drip irrigation - KUMAR, MUKESH; RAJPUT, T.B. S.; PATEL, NEELAM (Journal of Soil and Water Conservation, 2021)
Drip irrigation is an advanced and efficient method irrigation to use water efficiently. Water distribution in soil is one of the most important parameters to design efficient drip irrigation system. Soil texture, structure, initial soil moisture, and dripper discharge are the important factors on which extent of wetting front in soil mainly depends. An actual field research was conducted to investigate the effect of dripper discharge at different system operating pressures on spatio-temporal soil moisture movement. The value of moisture contents varied significantly (P<0.05) under different operating pressures (0.5, 1.0 and 1.5 kg/cm2) and at different locations below and away from the dripper. Highest values of soil moisture contents were observed below the drippers which decreased as the distance increased in both horizontal and vertical directions from the dripper. The values of moisture content in soil decreased as distance increase in both directions (horizontal and vertical) from the dripper. 9.4% and 14.3% higher values of soil moisture just below the dripper were observed with dripper discharges at 1.0 and 1.5 kg/cm2 system operating pressures respectively, as compared to dripper discharge at 0.5 kg/cm2 system operating pressure. Wetting front extended horizontally up to 15, 20 & 26 cm and vertically up to 30, 30 & 24 cm at dripper discharge at 0.5, 1.0 and 1.5 kg/cm2 system operating pressure, respectively after 1 day of irrigation.